Pengembangan Media Pembelajaran KOKAMI (Kotak Kartu Misterius) Pada Muatan IPA Untuk Krlas IV MI NWDI Pringgasela - Solihatun Solihatun; Muhammad Sururuddin; Mijahamuddin Alwi; Musabihatul Kudsiah (Jurnal Pendidikan Dasar, 2023)
Abstract: This study aims to develop learning media KOKAMI (Mysterious Card Box) on science content for class IV MI NWDI Pringgasela. The research method used is Research and Development (RD) with reference to the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) develop by Dicky and Carry. Based on the validation results, obtained the results of media validation with a total scoreof 37 with a score range of 33,96 37 â‰¤41,88, the â€œGoodâ€ category, and the validation results of media materials with a score 41 with a score range of 33,96 41 â‰¤41,88 in the â€œGoodâ€ category. As for the results of the small scale trial, the total score was 330 with an average score of 41,25 (33,96 41,25 â‰¤41) in the â€œGoodâ€ category. Student responses to a large scale trial on 28 students obtained a total score of 1.198 with an average score of 42, 78 (42,78 41,88) in the â€œVery Goodâ€ category. So with the results of this study it was concluded that the development of the KOKAMI media (Mysterious Card Box) on the developed science content was suitable for use in learning. Keywords: Media, KOKAMI, Science LearningAbstrak: Penelitian ini bertujuan untuk mengembangkan media pembelajaran KOKAMI (Kotak Kartu Misterius) pada muatan IPA kelas IV MI NWDI Pringgasela. Metode penelitian yang digunakan adalah Research and Development (R D) dengan mengacu pada model pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation) yang dikembangkan oleh Dick and Carry. Berdasarkan hasil validasi, diperoleh hasil validasi media dengan jumlah skor 37 dengan rentang skor 33,96 37 â‰¤41,88 kategori (â€œBaikâ€), dan hasil validasi materi media dengan skor 41 dengan rentang skor 33,96 41 â‰¤41,88 kategori (â€œBaikâ€). Adapun hasil uji coba skala kecil memperoleh jumlah skor 330 dengan rata-rata skor 41,25 (33,96 37 â‰¤41,88) dalam kategori â€œBaikâ€. Respon siswa pada uji coba skala besar pada 28 orang siswa diperoleh jumlah skor 1.198 dengan rata-rata skor 42,78 (42,78 41,88) dalamÂ kategori (â€œSangat Baikâ€). Sehingga dengan hasil penelitian ini disimpulkan bahwa pengembangan media KOKAMI (Kotak Kartu Misterius) pada muatan IPA yang dikembangkan layak digunakan dalam pembelajaran.Kata Kunci: Media, KOKAMI, Pembelajaran IPA